2023
DOI: 10.3390/healthcare11243194
|View full text |Cite
|
Sign up to set email alerts
|

Internet Addiction, Sleep Habits and Family Communication: The Perspectives of a Sample of Adolescents

Francisca Monteiro,
Margarida Simões,
Inês Carvalho Relva

Abstract: Background: With the increase in communication technologies, the internet has become an indispensable tool in the life of the individual. Several studies report on the advantages of this resource; however, there is still a group of individuals who use the internet excessively. The aim of this study was to explore the relationships between internet addiction, daytime sleepiness, and family communication in adolescents. Methods: A total of 340 adolescents aged between 12 and 17 years participated in this study. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 68 publications
(95 reference statements)
0
1
0
Order By: Relevance
“…A study conducted in Germany in 2022 showed that 43.69% of 12–17-year-old teenagers used the internet in problematic ways [ 21 ]. In Portugal, a study found that adolescents exhibit varying degrees of internet addiction: normal users (35.9%), users with mild addiction (47.9%), and users with moderate addiction (16.2%) [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted in Germany in 2022 showed that 43.69% of 12–17-year-old teenagers used the internet in problematic ways [ 21 ]. In Portugal, a study found that adolescents exhibit varying degrees of internet addiction: normal users (35.9%), users with mild addiction (47.9%), and users with moderate addiction (16.2%) [ 37 ].…”
Section: Discussionmentioning
confidence: 99%